Spiritual Distress In Breast Cancer Patients - Puji Lestari; Aan Nuraeni; Dyah Setyorini (Universitas Padjadjaran, 2018)
Breast Cancer would affect all aspects of patients’ life including spiritually. This aspect is one of the patients’ main coping sources in dealing with impacts of the disease. However, the spiritual aspect is rarely noticed by nurses, and may lead to patients’ spiritual distress. This study aimed to determine spiritual distress in breast cancer patients who had treatments in a referral hospital in West Java. This study was a descriptive quantitative with cross-sectional approach. The population was in-patient breast cancer patients. Respondents were chosen using the accidental sampling technique. During a month period, 37 patients involved in this study. The data was collected using an instrument which was developed from Spiritual Distress Assessment Tool (SDAT) and analyzed using descriptive quantitative analysis. Almost two-thirds (62.2%) of respondents had low spiritual distress, 32.2% of respondents had moderate spiritual distress and a very small number of respondents (5.4%) had severe spiritual distress. In the term of spiritual distress dimension, “life balance” had the highest mean score (1.86) and the lowest was in “values and beliefs with sub-dimension of need maintain control” (0.89). The conclusion was the majority of patients had low spiritual distress, yet spiritual distress for moderate to severe still could be found in smaller proportion. Life balance was dimension with the highest level of spiritual distress. The patients’ spiritual need would be achieved when patients have a good acceptance and adaptation. Nurses have a role to encourage patients’ acceptance of their illnesses through improvement of the fulfillment of the patient's spiritual needs.